ANALISIS PENERAPAN DAN PERLAKUAN AKUNTANSI MURABAHAH UNTUK PEMBIAYAAN KONSUMTIF - Ika Rahmadani (universitas teuku umar, 2017)
AbstractThis study aims to know the implementation of murabahah financing in PT. BankMuamalat Indonesia branch office Banda Aceh, such as the rule of murabahah financing,the procedure of murabahah financing, and accounting of Murabahah financing and the conformity of its implementation to Statement of Financial Accounting Standards (PSAK) No. 102. The study conducted by using a descriptive method. Descriptive method is to conclude, interpret and clarify the data in accordance with the actual events. The type of data used are primary data and secondary data that obtained from interviews with financing staff in PT Bank Muamalat Indonesia Branch Office Banda Aceh. The authors obtained the results of research with a conclusion that the practices in PT Bank Muamalat Indonesia Branch Office Banda Aceh is compliance with the Statement of Financial Accounting Standards (PSAK) No. 102. Kata kunci: pembiayaan murabahah, akuntansi pembiayaan murabahah, pembiayaan konsumen, PSAK 102